Events and predication : a new approach to syntactic processing in English and Spanish - Sanz, Montserrat (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2000)
Studies on the syntactic consequences of event type in languages have shown that Aktionsart plays a role in Universal Grammar. This book contributes to the exploration of the syntax/semantics interface by presenting a thorough comparison of event and predicate types in English and Spanish. The mapping between event and syntactic predicate types, including detransitives, is given a minimalist account based on the functional categories that embed event features and on a careful analysis of the features checked by objects. As the book delves into the theoretical issue of how parameters are charac.